The incidence of microscopic thyroglossal duct tissue superior to the hyoid bone. (8th September 2018) - Garcia, Erick; Osterbauer, Beth; Parham, David; Koempel, Jeffrey
Abstract : Objective: Despite the success of the Sistrunk procedure, persistence of a thyroglossal duct cyst (TGDC), sinus, or remnant following excision remains a clinical problem. This is most likely due to the presence of microscopic disease that was not excised at the time of surgery. The purpose of this study is to determine the incidence of microscopic disease superior to the hyoid bone in children who have had either a primary or revision procedure for a TGDC. Methods: A prospective review of pathologic specimens was conducted of all consecutive patients undergoing TGDC excision by pediatric otolaryngologists at the Children's Hospital Los Angeles beginning March 2014 through July 2017 in both primary and revision procedures. Results: Microscopic disease was present superior to the hyoid bone in 25 of the 34 (74%) specimens and in 100% (6) of the specimens from a revision procedure. Conclusion: The majority of persons who have a TGDC will have microscopic disease superior to the hyoid bone. In order to minimize the incidence of persistence following a primary procedure, tissue superior to the hyoid bone should be removed routinely even if no gross disease is noted at the time of surgery. When performing a revision procedure, special attention should be given to the suprahyoid area as a likely site of persistent disease. Level of Evidence: 2b Laryngoscope, 129:1215–1217, 2019